Fiscal Federalism In The 21st Century Nigeria And Its Challenges On Sustainable Development Of The Federation - Amos Ojo Adedeji, Ph.D (International Journal of Technology and Education Research, 2023)
Fiscal federalism is a political arrangement for federating units to interact fiscally in the realization of government goals and objectives. The constitution clearly stipulate and demarcate the powers and functions of each units of the federation of Nigeria. However, the sharing formula is always competitive. The study qualitatively x-ray fiscal federalism in the 21st century Nigeria and its challenges on sustainable development. Many challenges, including the overly centralized federal government, poor financial management, and overdependence on oil, among others, have hampered Nigeria's fiscal relations. The study concluded by recommending decentralization of powers, eradication of corruption and diversify of economy. Consistent and workable revenue allocation formula is also apt in addressing the menace hinder fiscal relation in the federation.